Post-COVID educational leadership: Emerging models and styles for a new era - Karimi, Hengameh; Khawaja, Sarwar (International Journal of Innovative Research and Scientific Studies, 2025)
Modern educational leadership is a cornerstone of institutional effectiveness, requiring a compelling vision, clear goals, and strategic planning. The COVID-19 pandemic disrupted education systems worldwide, exposing significant weaknesses in leadership models and crisis preparedness. Many institutions struggled to adopt effective strategies to address the challenges of sudden shifts in teaching modalities, technological demands, and stakeholder concerns. While crisis management has been widely studied in other contexts, there is a distinct lack of empirical research focusing on educational leadership during crises. This study aims to bridge that gap by employing the PRISMA methodology to systematically review scholarly articles published between 2019 and 2022. It explores the challenges faced by educational leaders, the crisis management strategies implemented, and the personality traits that contributed to effective leadership during this disruptive period. By synthesizing these findings, the study highlights critical lessons in leadership and crisis management, offering practical recommendations for fostering resilience and adaptability in educational institutions to face future challenges.